Current status of Crimean-Congo haemorrhagic fever in the World Health Organization Eastern Mediterranean Region: issues, challenges, and future directions. (May 2017) - Al-Abri, Seif S.; Abaidani, Idris Al; Fazlalipour, Mehdi; Mostafavi, Ehsan; Leblebicioglu, Hakan; Pshenichnaya, Natalia; Memish, Ziad A.; Hewson, Roger; Petersen, Eskild; Mala, Peter; Nhu Nguyen, Tran Minh; Rahman Malik, Mamunur; et al.
Highlights: The paper provides a comprehensive overview of the status of Crimean-Congo hemorrhagic fever (CCHF) in countries across the World Health Organization Eastern Mediterranean Region (WHO EMR). The increasing incidence of CCHF disease in the region and its spread to new geographical areas is highlighted. Knowledge gaps concerning the burden and circulation of CCHF virus in the WHO EMR are identified. A strategic framework is described, which details the research and development work necessary to curb the ongoing and new threats posed by CCHF virus. Summary: Crimean-Congo haemorrhagic fever (CCHF) is the most widespread, tick-borne viral disease affecting humans. The disease is endemic in many regions, such as Africa, Asia, Eastern and Southern Europe, and Central Asia. Recently, the incidence of CCHF has increased rapidly in the countries of the World Health Organization Eastern Mediterranean Region (WHO EMR), with sporadic human cases and outbreaks of CCHF being reported from a number of countries in the region. Despite the rapidly growing incidence of the disease, there are currently no accurate data on the burden of the disease in the region due to the different surveillance systems used for CCHF in these countries. In an effort to increase our understanding of the epidemiology and risk factors for the transmission of the CCHF virus (CCHFV; a Nairovirus of the family Bunyaviridae ) in the WHO EMR, and to identify the current knowledge gaps that are hindering effective control interventions, a sub-regional meeting was organized in Muscat, Oman, from December 7 to 9, 2015. This article summarizes the current knowledge of the disease in the region, identifies the knowledge gaps that present challenges for the prevention and control of CCHFV, and details a strategic framework for research and development activities that would be necessary to curb the ongoing and new threats posed by CCHFV.